INTERSUBJEKTIVITAS, CINTA DAN KESETIAAN DALAM FILM HABIBIE & AINUN (PERSPEKTIF EKSISTENSIALISME GABRIEL MARCEL) - Qomariah, Siti (Faculty of Ushuluddin and Humanities, 2015)
This study is based on the appearance of the film Habibie & Ainun which managed to attract the attention ofÂ the public to watch. This love-themed movie that became a phenomenon for some people and have managed toÂ beat films that also betema other love. Moreover, many people who think that the film preformance characterÂ (Habibie and Ainun) is a reflection of the couple are ideal. When reading the title of the film, Habibie &Â Ainun seemed to have in common with âRomeo and Julietâ which is one of the famous love story of all time,Â and when he saw the banner of the film that contains the image of two lovebirds have led to the concept that thisÂ film is a film about love. The image of romance has been able to anesthetize the eyes of anyone who saw it,Â makes the heart to see it immediately, while steeped in positive values implicit in his every scene. To doÂ âreadingsâ or interpretations of the movie Habibie & Ainun, certainly needed a knife analysis, one analysisÂ of existentialism, particularly existentialist Gabriel Marcel. By doing so, will make it easier to determine aÂ range of values or messages hidden behind it.